Extreme points and rotundity of Orlicz-Sobolev spaces. (2002) - Chen, Shutao; Hu, Changying; Zhao, Charles Xuejin
Abstract : It is well known that Sobolev spaces have played essential roles in solving nonlinear partial differential equations. Orlicz-Sobolev spaces are generalized from Sobolev spaces. In this paper, we present sufficient and necessary conditions of extreme points of Orlicz-Sobolev spaces. A sufficient and necessary condition of rotundity of Orlicz-Sobolev spaces is obtained.